Gambaran Penyakit Jantung Berdasarkan Demografi Dan Penggunaan Obat - Nur Hasanah; Fadly Putajaya; Lela Kania; Nur Wulan Adi Ismaya; Nanda Nurul Aini (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2021)
The heart is one of the important organs in the human body. With the abnormality of heart organ function, it can cause heart and vascular disease, heart and blood vessel disease is the number 1 cause of death globally and is a non-communicable disease. Risk factors for heart and vascular disease increase with age, unhealthy lifestyle, heavy smokers, stress and a history of diseases in the family. This study aims to find out the spread of patients with heart disease in X Hospital, South Tangerang city in the period 2015 to 2019 based on the after, gender and medications often prescribed by doctors for patients with heart disease. The type of research conducted is descriptive, using secondary data sources obtained from medical record data, and prescription sheets. The sample number of 477 patients out of a total population of 10,623 patients, the results showed gender in males (72%), the most age over 65 years or seniors (48%), drugs often prescribed by doctors are Clopidogrel and Bisoprolol. From the data can be concluded with a healthy lifestyle can maintain the health of the body, especially the heart, and prolong the productive life of a person.